2010
DOI: 10.1080/13674670903357844
|View full text |Cite
|
Sign up to set email alerts
|

Can “sense of presence” experiences in bereavement be conceptualised as spiritual phenomena?

Abstract: Can "sense of presence" experiences in bereavement be conceptualised as spiritual phenomena?This paper explores the possibility of conceptualising the frequently occurring experience of "sensing the presence of the deceased" in bereavement as a spiritual phenomenon and examines how such a conceptualisation can be related to two recent perspectives in the field of bereavement research, "continuing bonds" and "meaning-making". It is argued that "sense of presence" experiences are expressions of the continuing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
1
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 101 publications
4
49
1
12
Order By: Relevance
“…These supernatural events may operate as imaginal attachment resources that support a sense of "earned security" and emotional regulation (Granqvist, Mikulincer, & Shaver, 2010). Optimally, spiritual or religious beliefs may offer greater meaning making (Frick, 2011;Steffen & Coyle, 2010;Steffen & Coyle, 2011) and a continuing bond with the deceased, whether externalized (hallucinations and illusions of the deceased) or internalized (mental representations of the deceased) (Field, 2006;Field, Gao, & Paderna, 2005).…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 98%
“…These supernatural events may operate as imaginal attachment resources that support a sense of "earned security" and emotional regulation (Granqvist, Mikulincer, & Shaver, 2010). Optimally, spiritual or religious beliefs may offer greater meaning making (Frick, 2011;Steffen & Coyle, 2010;Steffen & Coyle, 2011) and a continuing bond with the deceased, whether externalized (hallucinations and illusions of the deceased) or internalized (mental representations of the deceased) (Field, 2006;Field, Gao, & Paderna, 2005).…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 98%
“…In a recent review of the literature, it was suggested that socially sanctioned conceptual frameworks need to be available for the meaningful integration of these experiences and the possible occurrence of post-traumatic growth (Steffen & Coyle, 2010).…”
mentioning
confidence: 99%
“…Frost and S.-M. Nolas and methodological experimentations have taken place, they have been used constructively to study complexities of human experience (e.g., Johnson, Burrows & Williamson 2004). Such pluralistic approaches have been found to be valuable in exploring topics of particular ontological challenge (e.g., paranormal experience; Steffen & Coyle 2010). Researchers have focussed on the role of pluralism in triangulation (Moran-Ellis et al 2006) and in multiple data sources in seeking further understanding of a phenomenon (e.g., Dicks, Soyinka & Coffey 2006).…”
mentioning
confidence: 99%